Analisis Perancangan SIA Penjualan Jasa Listrik Menggunakan Kerangka BABOK 3.0 (Studi Kasus Pada Perusahaan Jasa Konstruksi PT. Cupuintan Adyapermata) - Ilham Zharfan Satrya; Rendra Trisyanto Surya; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2023)
In this final project will analyze the old sales accounting system and design a sales AIS at the construction service company PT. Cupuintan Adyapermata. The framework used in this research is the latest framework, namely the SDLC version BABOK 3.0 method for easier implementation of sales accounting information systems in the company. The results show that there are weaknesses in the old Electricity Sales AIS, namely uncollectible accounts and often late in payments. . In terms of design, AIS at the company, the author will design to reinforce procedures related to billing and accounts receivable and the Age Analysis Report used by the company's management as a basis for later decision making with flowcharts and physical DFD. Thus these recommendations will create a new quality sales AIS at PT. Cupuintan Adyapermata so as to facilitate the management of the company's sales accounting.